A Pilot Study of the Effect of Otago Exercise Program on Fall Risk and Quality of Life of Older Women - Muammar Irsyad Kadir; Nur Hardiyanty; Fadhia Adliah (Universitas Udayana dan Diaspora Taipei Medical University, 2021)
Objective: This study aims to determine the effect of the Otago Exercise Program on the risk of falling and the quality of life of older people. Methods: The method used was experimental research with pretest-posttest design and control group design, involving 16 participants. Before and after treatment, respondents measured the risk of falling using a Timed-Up-and-Go test (TUGT) and quality of life using the World Health Organization Quality of Life BREF (WHOQL-BREF). Furthermore, the obtained data were analyzed using the paired T-test and independent T-test. Results: The results showed a significant effect on the risk of fall and the quality of life of the older people in the treatment group. In addition, there were significant different influences on the value of falling risk and quality of life (physical and environmental) between the treatment and control groups. Conclusion: The Otago exercise program had a significant effect on reducing the risk of falls and improving the quality of life of older people.